2016
DOI: 10.1016/j.molcel.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin Releases DNA through Asymmetric ATPase-Driven Ring Opening

Abstract: SummaryCohesin stably holds together the sister chromatids from S phase until mitosis. To do so, cohesin must be protected against its cellular antagonist Wapl. Eco1 acetylates cohesin’s Smc3 subunit, which locks together the sister DNAs. We used yeast genetics to dissect how Wapl drives cohesin from chromatin and identified mutants of cohesin that are impaired in ATPase activity but remarkably confer robust cohesion that bypasses the need for the cohesin protectors Eco1 in yeast and Sororin in human cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
138
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(154 citation statements)
references
References 42 publications
15
138
0
1
Order By: Relevance
“…Intriguingly, a large fraction of chromatid-bound cohesins are removed during prophase in a proteolytic-independent process that requires SA1,2/Scc3 phosphorylation [35,61]. Identifying the “gate” or subunit pair that regulates cohesin dynamics, however, is obfuscated by conflicting evidence and potentially distinct entry and exit reactions [47,62,63], reminding us that we remain in the early stages of cohesin research. Regardless, elucidating the enzymology of cohesins in different parts of the cell cycle is vital to resolve transition states through which both adaptable and stable cohesin populations are simultaneously achieved.…”
Section: Cohesin Enzymology: Is It Only About Gates?mentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, a large fraction of chromatid-bound cohesins are removed during prophase in a proteolytic-independent process that requires SA1,2/Scc3 phosphorylation [35,61]. Identifying the “gate” or subunit pair that regulates cohesin dynamics, however, is obfuscated by conflicting evidence and potentially distinct entry and exit reactions [47,62,63], reminding us that we remain in the early stages of cohesin research. Regardless, elucidating the enzymology of cohesins in different parts of the cell cycle is vital to resolve transition states through which both adaptable and stable cohesin populations are simultaneously achieved.…”
Section: Cohesin Enzymology: Is It Only About Gates?mentioning
confidence: 99%
“…Thus, mutations in Smc1 can abrogate Smc3 ATP hydrolysis and vice versa. Moreover, Smc1,3 are asymmetrically positioned within the cohesin complex, and individual ATP hydrolysis cycles appear similarly asymmetric in terms of cohesin function [18,21,62,63,66]. Thus, how ATP binding and hydrolysis and acetylation impact deposition and stability remain exciting frontiers in cohesin research.…”
Section: Cohesin Enzymology: Is It Only About Gates?mentioning
confidence: 99%
“…The SMC3 expression constructs randomly integrated in the genome had an HA tag for convenient detection and were expressed from a β-actin promoter. Importantly, exogenously expressed wild-type SMC3-HA-but not an ATPasedead mutant of SMC3 (SMC3-K38I) previously shown to be required for viability (Elbatsh et al 2016)-compensated for the proliferation defects of Auxin-treated SMC3 −/3AID6Flag cells (Supplemental Fig. S3A).…”
Section: Addition Smc3mentioning
confidence: 88%
“…Another possibility is that the actual agent of MukB ATPase activity is a conglomerate of MukB dimers associated head-to-head and that the MukF dimer need only bind to one end of the chain to trigger ATP hydrolysis throughout. A recent study of DNA release by the yeast cohesin showed that asym- metric ATP hydrolysis by the head domains of Smc1 and Smc3 was involved (32). Perhaps the head domains in a MukB dimer are also non-equivalent.…”
Section: Topological Alteration Of the Dna Observed In The Reactionsmentioning
confidence: 99%